Extracorporeal shockwave increases the effectiveness of systemic antibiotic treatment in implant‐related chronic osteomyelitis: Experimental study in a rat model. Issue 6 (20th February 2014) - Inanmaz, Mustafa Erkan; Uslu, Mustafa; Isik, Cengiz; Kaya, Ertugrul; Tas, Tekin; Bayram, Recep
<x xml:space="preserve">Abstract</x> Implant‐related chronic osteomyelitis is a serious complication of orthopedic surgery requiring implant removal and radical debridement. Extracorporeal shockwave (ESW) have demonstrated significant bactericidal effectiveness in vitro and effectiveness and safety were evaluated in an animal model of osteomyelitis. In this experimental study, we aimed to test our hypothesis that the use of ESW together with systemic antibiotic treatment will provide synergy for the treatment of implant‐related chronic osteomyelitis caused by methicillin‐susceptible Staphylococcus aureus (MSSA). The proximal tibia of 32 rats was contaminated with 108 CFU/ml methicillin‐sensitive S. aureus (MSSA‐ATCC 29213) and Kirschner‐wires were placed into the medulla of the tibia. After 4 weeks, Kirschner‐wires were removed and the rats were randomly divided into four groups: group I, untreated contaminated control group; group II, receiving only ESW therapy; group III, receiving only systemic teicoplanin; group IV, treated with a combination of ESW and systemic teicoplanin. ESW was applied twice to the infected limbs and all rats were sacrificed at the end of 8th week. The degree of tibial osteomyelitis was assessed by quantitative culture analysis. Bacterial counts in groups III and IV were significantly reduced relative to the control (p = 0.002 and 0.001, respectively). The decrease in bacterial counts was more pronounced and significant in group IV compared to group III (p = 0.024). In group II, bacterial counts also decreased, but the differences were in significant (p = 0.068). Our experimental model suggests that ESW provides significant synergy for systemic antibiotic treatment. However, further clinical trials are required in order to use this treatment modality safely in patients, even though our study demonstrated successful results in the treatment of implant‐related chronic osteomyelitis in rats. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:752–756, 2014.